Just pursuit: a black prosecutor's fight for fairness - Coates, Laura (Simon & Schuster)
Please don't come : on what happens when a black woman must aid in a deportation arrest -- Wanna see something funny? : on being trained by a white colleague how to interrogate a black defendant -- I want no part of this : on the older black woman victim who pleads for lenience for a young black defendant -- She needed me to believe her : on the domestic assault victim afraid to be judged -- That's not me : on the real case of mistaken identity -- A seat at the (right) table : on the tension between black public defenders and prosecutors -- Babyface : on the conviction of a baby-faced defendant who acts against his self-interest -- There's still time : on prosecuting a mother for child abuse while faced with the prospect of losing my own -- Not their son, too : on watching the victim's family beg not to have their son's murderer go to prison -- No one who had been raped would have ever : on watching a judge shame a teenage sexual assault victim based on her courtroom attire -- She's always been such a good girl : on cross-examining a naive and helpless mother trying to defend her daughter on trial -- Grandstanding for justice -- The chew : on the role of privilege in charging decisions -- I just don't believe in it : on the tension between illegal and wrong -- Chess pie : on a prosecutor embraced outside of the courtroom -- It didn't have to happen to me : on the haunting effect of secondary trauma -- Conclusion.